Changes in Fungal Communities across a Forest Disturbance Gradient - Shi, Lingling (Appl Environ Microbiol, 2019)
Deforestation has a substantial impact on aboveground biodiversity, but the response of belowground soil fungi remains poorly understood. In a tropical montane rainforest in southwestern China, plots were established along a forest degradation gradient ranging from mature and regenerated forests to open land to examine the impacts of forest degradation and deforestation on ecosystem diversity and function. Here, we evaluated the changes in belowground fungal diversity and community composition using a metabarcoding approach. Soil saprotrophic fungal richness declined with increasing forest disturbance. For example, Penicillium spp. (phosphorus [P]-solubilizing fungi) dominated in mature forest but were less abundant in regenerating forests and showed the lowest abundance in open land sites. Conversely, the abundance of facultative pathogenic fungi increased along the disturbance gradient. The decline in soil saprophytic fungi may be a direct result of forest disturbance or it may be associated with increased availability of soil phosphorus indirectly through an increase in soil pH. The increase in abundance of facultative pathogenic fungi may be related to reduced competition with saprotrophic fungi, changes in microclimate, or increased spore rain. These results demonstrate a loss of dominant P-solubilizing saprotrophic fungi along the disturbance gradient, indicating a change from soil P limitation in mature tropical forests to soil C limitation in deforested sites. The increased prevalence of pathogenic fungi may inhibit plant succession following deforestation. Overall, this research demonstrates that soil fungi can be used as a sensitive indicator for soil health to evaluate the consequences of forest disturbance. IMPORTANCE The soil fungal functional group changes in response to forest disturbance and indicates a close interaction between the aboveground plant community and the belowground soil biological community. Soil saprotrophic fungi declined in relative abundance with increasing forest disturbance. At the same time, the relative abundance of facultative pathogenic fungi increased. The loss of saprotrophic fungal richness and abundance may have been a direct result of forest disturbance or an indirect result of changes in soil pH and soil P. Furthermore, the dominant P-solubilizing saprotrophic fungi were replaced by diverse facultative pathogenic fungi, which have weaker C decomposition ability. These changes potentially indicate a shift from soil phosphate limitation to carbon limitation following deforestation. This study suggests that changes in fungal functional group composition can be used as an indicator of the effects of forest disturbance on soil carbon and nutrients.